Percutaneous Fetal Cardiac Interventions for Structural Heart Disease - Schidlow, David N. (Am J Perinatol, 2014)
INTRODUCTION: Prenatal diagnosis provides valuable information regarding a variety of congenital heart defects. Some defects occur early in gestation with little change throughout pregnancy, whereas others evolve during mid and late gestation. Fetal cardiac intervention (FCI) affords the opportunity to interrupt progression of disease in this latter category, resulting in improved perinatal and lifelong outcomes. AIM: This chapter addresses three lesions for which percutaneous FCI can be utilized: (1) aortic stenosis with evolving hypoplastic left heart syndrome, for which aortic valvuloplasty may prevent left ventricular hypoplasia and has yielded a biventricular circulation in approximately one third of cases; (2) hypoplastic left heart syndrome with intact atrial septum, for which relief of atrial restriction has potential to improve perinatal survival; and (3) pulmonary atresia with intact ventricular septum and evolving right ventricular hypoplasia, for which pulmonary valvuloplasty has resulted in a biventricular circulation in the majority of patients. The pathophysiology, rationale for intervention, patient selection criteria, procedural technique, and outcomes for each lesion will be reviewed. This chapter will also review complications of FCI and their treatment, and maternal and fetal anesthesia specific to FCI. The importance of a specialized center with experience managing infants delivered after FCI will also be addressed.